Nine new species of the genus Pholcus Walckenaer (Araneae: Pholcidae) from South Korea - Lee, Jun-Gi; Lee, Jun-Ho; Choi, Doo-Yeong; Park, Sun-Jae; Baek, Min-Jeong; Kim, Sam-Kyu (Zootaxa, 2024)
Nine new species belonging to the Pholcus phungiformes-group are described from Korea, viz., Pholcus chugok Lee & Lee, sp. nov., Pholcus noeun Lee & Lee, sp. nov., Pholcus wonju Lee & Lee, sp. nov., Pholcus ungyo Lee & Lee, sp. nov., Pholcus hwangjeong Lee & Lee, sp. nov., Pholcus gimsatgat Lee & Lee, sp. nov., Pholcus solchi Lee & Lee, sp. nov., Pholcus mino Lee & Lee, sp. nov., and Pholcus maepo Lee & Lee, sp. nov. These new species were found from mountainous habitats in Gangwon-do and Chungcheongbuk-do, the northeastern regions of South Korea where the two major mountain ranges (Taebaeksan mountains and Sobaeksan mountains) are located together. Detailed descriptions, photographs, and a distribution map for the new species are provided with notes on their intraspecific variations of copulatory organs.